Generation of human induced pluripotent stem cell lines from a subject with UBAP1L-associated retinal dystrophy and CRISPR/cas9-corrected isogenic iPSC lines - Andréa Amprou; Tasnim Ben Yacoub; Camille Letellier; Vincenzo Degaetano; Cécile Méjécase; Leila Azizzadeh Pormehr; Christel Condroyer; Amélie Slembrouck-Brec; Juliette Wohlschlegel; Olivier Goureau; Christina Zeitz; Isabelle Audo (Stem Cell Research)
A Human induced pluripotent stem cell (iPSC) line was generated from dermal fibroblasts of a patient affected with an autosomal recessive retinal dystrophy carrying the homozygous c.910-7G>A variant in UBAP1L. Three isogenic control iPSC lines derived from this affected subject line were created using CRISPR/Cas9 engineering. All iPSC lines expressing the pluripotency markers, were able to differentiate into the three germ layers, and exhibit a normal karyotype. These cellular models will provide a powerful tool to study disease mechanisms associated with the recently reported UBAP1L- associated retinal dystrophy and better understand the role of the protein in retinal physiology.